Detection of Estrogen-Independent Growth-Stimulating Activity in Breast Cancer Tissues: Implication for Tumor Aggressiveness - Yamaguchi, Yuri (Springer Netherlands, 2013)
Estrogen and various growth factors affecting tumor behavior are present in the breast cancer microenvironment, but their comprehensive effects and signal crosstalks are different in each case. However, there is no system to evaluate the factors, detected in individual breast cancer cases, that regulate ER activity and tumor progression. In this study, we analyzed the effects of individual breast cancer extracts by our original system using an estrogen-signal reporter cell line, MCF-7-E10, which we previously established. MCF-7-E10 cell line is stably transfected by an estrogen response element (ERE)-green fluorescent protein (GFP) gene; it expresses GFP when estrogen receptors (ERs) are activated by estrogen or growth factor signal-mediated ER phosphorylation. Using this cell line, we analyzed the comprehensive effects of factors derived from breast cancer tissues on ER activity and growth of MCF-7-E10 cells for each case. We also analyzed relationships between these activities and clinicopathologic characteristics of patients who provided cancer specimens. The breast cancer extracts, which reflect the combined activities of growth factors present in individual cases, stimulated MCF-7-E10 cell growth in an estrogen-independent manner, and specifically stimulated growth of other breast cancer cell lines, regardless of ER expression. High growth-promoting activities were seen in tumor regions of specimens with tumors > 10 mm in size, HER2 intrinsic subtype, and scirrhous and solid-tubular carcinoma histological subtypes. Anti-human hepatocyte growth factor (HGF) antibody and an inhibitor for insulin-like growth factor-1 (IGF-1) receptor inhibited MCF-7-E10 cell growth by the breast cancer extracts, indicating that signal pathways via HGF or IGF-1 receptor significantly affect breast cancer. These data suggest that growth factors other than estrogen in the tumor extract significantly affect breast cancer aggressiveness in an estrogen-independent manner, and could be useful therapeutic targets.